PERANAN RUANG PUBLIK DALAM KEHIDUPAN MASYARAKAT MULTIKULTURAL - Hendrikus Triwibawanto Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Indonesia has many religions, ethnics, tribes, local languages, and race, as national culture wealth for we must be greatfull. Nevertheless, those culture wealth also keep tacit potency conflict, riot, civil war, even murder among society. It is more complicated because irresponsible political elites exploite this condition for sake of politics. Multicultural that is actually our national pride, can become “time bomb” that sometimes can endanger our national unity. In this context, Habermas a Germany Philosopher has offered a brilliant idea about the importance of public sphere to develop good coexistence. How the idea could give contribution of solution in multicultural nation? This Article tries to elaborate it.